2019
DOI: 10.1108/rbf-03-2019-0044
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of behavioral biases affecting investment decision making of individual equity investors by fuzzy analytic hierarchy process

Abstract: Purpose Research in the area of behavioral finance has demonstrated that investors exhibit irrational behavior while making investment decisions. Investor behavior usually deviates from logic and reason, and consequently, investors exhibit various behavioral biases which impact their investment decisions. The purpose of this paper is to rank the behavioral biases influencing the investment decision making of individual equity investors from the state of Punjab, India. This research would provide valuable insig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
124
5
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 61 publications
6
124
5
10
Order By: Relevance
“…Referring to the prospect theory, this is possible because investors think that the investment made is more like a choice between the gain and loss of investment. The results of this study support the research conducted by Aziz & Khan (2016), but does not support the results of research conducted by Cherono et al, (2019); Hunguru et al (2020); Isidore R & Christie (2019); Jain et al, (2019);S Hallale & Gadekar (2019). This difference is possible due to cultural differences, differences in the age of respondents, and differences in existing technological developments so that technological advances have an important role in disseminating information to investors.…”
Section: Overconfidence (O)contrasting
confidence: 95%
See 2 more Smart Citations
“…Referring to the prospect theory, this is possible because investors think that the investment made is more like a choice between the gain and loss of investment. The results of this study support the research conducted by Aziz & Khan (2016), but does not support the results of research conducted by Cherono et al, (2019); Hunguru et al (2020); Isidore R & Christie (2019); Jain et al, (2019);S Hallale & Gadekar (2019). This difference is possible due to cultural differences, differences in the age of respondents, and differences in existing technological developments so that technological advances have an important role in disseminating information to investors.…”
Section: Overconfidence (O)contrasting
confidence: 95%
“…In the related analysis, Samuelson & Zeckhauser (1988) introduced the term "status quo bias" after documenting the tendency to maintain the status quo in decision making. Previous research examining the relationship of loss aversion to investment decisions has had various results such as Cherono et al (2019); Hunguru et al (2020); Isidore R & Christie (2019) shows a significant relationship of loss aversion to investment decisions, and S Hallale & Gadekar (2019) indicates a weak relationship, meanwhile Aziz & Khan (2016); and Jain et al (2019) results that there is no relationship between loss aversion and investment decisions. Furthermore, in this study will discuss these financial behaviors towards community investment decisions, especially investments in capital market.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other researchers have demonstrated that family firms often find these changes unwanted and radical (Broadbent et al , 2001; Gross and Geiger, 2017). Bourdon and Jaouen (2016), Oreg (2018), Baker et al (2019) and Jain et al (2019) highlight that the potential of resistance to change should reduce in confidence biases to a more compressive in working capital management. This research focusses on resistance to change in the financial management of Laotian family firms.…”
Section: Introductionmentioning
confidence: 99%
“…Though there are several biases which impact upon investors' decision making but we have selected certain major biases which are supposed to influence the investors' behavior in the emerging markets. Jain, Walia, and Gupta (2019) ranked the behavioral biases which influence the investors' decision making in India. Where they applied Fuzzy analytic hierarchy process to rank the factors influencing the retail investors' decision making.…”
Section: Introductionmentioning
confidence: 99%